DEVELOPMENT OF ANIMATED VIDEO MEDIA TO IMPROVE LEARNING MOTIVATION AND CHARACTER OF EARLY CHILDHOOD STUDENTS - Nuni, Nuni Wahyuningsi; Kurniawati, Neneng; Nurhayati, Nurhayati; Herpratiwi, Herpratiwi (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
Education is an action to improve the life of the nation. There is a relationship between the idea of ​​improving the life of the nation and its implementation, which can be achieved through various means, such as curriculum development, teacher preparation through pre-service education, teacher education and training on the job, the teacher development system in the workplace, the training process, especially in choosing learning strategies and implementing educational assessments. Several factors influence the success of learning to use strategies in education. Teachers' work is not the only source of learning. Teachers' ability to choose learning strategies to increase the achievement of learning goals, which refer to student achievement in class, is part of their job. Various strategies are designed and evaluated to improve student learning. This research aims to (1) Create learning media; and (2) explain how animated videos function to increase learning motivation and character of group B students at Kemala Bhayangkari 04 Kindergarten, Bogor City. The research method used refers to the ten steps developed by Borg & Gall, which consist of a preliminary study; planning; initial product development; initial trials; initial product revisions; field trials; revision of field trial results; operational trials; and revision of the final product. The products that have been developed are tested using quasi-experimental methods. Using the t test, it is known that animated videos increase students' motivation to learn and their character. Effectiveness can be seen from the average value of learning motivation and the character of students in group A and group B which are very different before and after using animated video media in learning. Keywords: animated video media, learning motivation, student character